2003
DOI: 10.1186/bcr593
|View full text |Cite
|
Sign up to set email alerts
|

The role of androgens and polymorphisms in the androgen receptor in the epidemiology of breast cancer

Abstract: 164 AR = androgen receptor; BMI = body mass index; CAG = cytosine adenine guanine; GGC = guanine guanine cytosine. Breast Cancer Research Vol 5 No 3 Lillie et al. IntroductionThe role of androgens in breast cancer etiology has been a subject of both curiosity and confusion. It is still unclear by which mechanisms testosterone exerts its activity in the female breast, and whether the effects are predominantly proliferative or anti-proliferative on breast cells at physiologic levels. In the present review we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 69 publications
(98 reference statements)
5
43
0
Order By: Relevance
“…Clearly, the cumulative epidemiologic data to date leave the effect of androgens on breast cancer risk unresolved. 3 Moreover, data from cell culture and in vitro studies are inconclu- [4][5][6] The only previous study of androstenediol in relationship to breast cancer risk of which we are aware reported a positive association, consistent with our results, but the association was not adjusted for estrogens. 7 Our finding of a slight reduction in risk with increasing levels of SHBG, although not statistically significant, is similar to that from the reanalysis of the 9 prospective studies, 2 an expanded version of 2 of these studies 24,25 and other recent cohort studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Clearly, the cumulative epidemiologic data to date leave the effect of androgens on breast cancer risk unresolved. 3 Moreover, data from cell culture and in vitro studies are inconclu- [4][5][6] The only previous study of androstenediol in relationship to breast cancer risk of which we are aware reported a positive association, consistent with our results, but the association was not adjusted for estrogens. 7 Our finding of a slight reduction in risk with increasing levels of SHBG, although not statistically significant, is similar to that from the reanalysis of the 9 prospective studies, 2 an expanded version of 2 of these studies 24,25 and other recent cohort studies.…”
Section: Discussionsupporting
confidence: 82%
“…1 The relationship between endogenous androgen levels (testosterone, androstenedione, dehydroepiandrosterone (DHEA)) and breast cancer risk is less clear, with both epidemiologic and experimental data providing conflicting results. [2][3][4][5][6] A metabolite of DHEA, 5-androstene-3b, 17b-diol (androstenediol), which in vitro acts as an estrogen in estradiol-deficient medium and as an androgen in an estrogen-rich medium, has been linked to increased breast cancer risk in postmenopausal women in one study. 7 Androgens could act to stimulate the breast directly or indirectly by providing the raw material for the synthesis of estrogens in peripheral or mammary adipose tissue.…”
mentioning
confidence: 99%
“…The tumor growth -inhibitory effects of testosterone and dihydrotestosterone have been observed in breast cancer cell lines and in animal models (1), whereas higher circulating androgen levels have been noted in breast cancer patients compared with controls (2,3). Androgen and estrogen levels are highly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…Other hormones, such as progesterone, prolactin and testosterone may also be important. 6,11,12 This work explores the evidence in literature that exposure to animal oestrogen is a major determinant of risk breast cancer. It is not intended to be a comprehensive review, but focuses narratively on epidemiological and experimental data relating to the implication of oestrogen in the aetiology of breast cancer and possible mechanisms that might account for the association.…”
Section: Introductionmentioning
confidence: 99%